Educational Simulation of Hull Deflection in Ro-Ro Ferry Vessels: Analyzing Hydrostatic Pressure with Variations in Plate Thickness and Seawater Depth - Istiqomah, Rika; Rozak, Dewi Nur Lathifa Abdul; Sitanggang, Renata Kantate Getsemani; Fatmawati, Alifah Widya (Current STEAM and Education Research, 2024)
The construction system is one of the most considered aspects in designing a ship, as the strength of the structure is the most crucial element that ensures the safety of the crew, passengers, and cargo carried. The ship's construction design must be able to withstand various loads or forces, both from inside and outside the ship. The purpose of this study is to determine the deflection of the Ferry Ro-Ro hull due to hydrostatic pressure with variations in plate thickness and seawater depth. This research uses modeling of the Ro-Ro ferry plate deflection due to seawater hydrostatic pressure with the finite difference method. The simulation results show that increasing the plate thickness from 10.0 mm, 15.0 mm, 20.0 mm to 25.0 mm significantly reduces the hull deflection, with the maximum deflection from about 2400 mm decreasing to less than 500 mm. In addition, the water depth also affected the deflection, where an increase in depth from 5 m, 10 m, and 15 m, caused the maximum deflection to increase from about 150 mm to 450 mm. The deflection pattern is parabolic with the maximum deflection occurring at the center of the ship, as the largest hydrostatic pressure distribution is at the center of the ship.